Waterpipe vs. Cigarette Smoking: Respiratory Health Risks among Youth - Imadi, Sara; Ali, Shara M.; Khodabocus, Jehan; Kullar, Savroop (Université d'Ottawa | University of Ottawa, 2015)
Waterpipe, or shisha, smoking is a popular traditional method of tobacco use, particularly in the Middle Eastern region and has become a global phenomenon. The smoke passes through a reservoir of water, shisha tobacco smoking is perceived as being less harmful than other methods of tobacco use. Recent evidence suggests that shisha smoking may be as addictive and as lethal as conventional cigarette smoking. Using the Cochrane library and PubMed, a systematic-like review will be conducted to analyze the literature to determine the presence or absence of a link between waterpipe smoking and the development of respiratory diseases in comparison to smoking from a cigarette. From the literature used for systematic-like analysis, primarily from the Middle East, we have found that the risk associated with the development of respiratory diseases from a waterpipe smoking are relatively equivalent to that of smoking cigarettes.